Locus specific epigenetic modalities of random allelic expression imbalance - Lucile Marion-Poll (Nature Portfolio, 2021)
Some autosomal genes are expressed in a random monoallelic manner, but its extent and mechanisms have remained unclear. Here the authors show robust monoallelic expression in cell lines and mice, where the silent allele can be reexpressed using epidrugs. Further, they find these genes display various modalities of allelic expression with different degrees of allelic imbalance.